Spectroscopic Tracking of the Characteristics of Microplastic-Derived Dissolved Organic Matter - Mengna Yuan; Huiqing Xiang; Yang Tong; Kanggen Zhou; Changhong Peng; Wei Chen (Separations, 2023)
Microplastic-derived dissolved organic matter (MP-DOM) has received increasing attention in recent years. In this study, the fluorescence excitation-emission matrix (EEM) combined with parallel factor analysis (PARAFAC) was used to track the leaching behavior of polyethylene (PE), polyvinyl chloride (PVC), polypropylene (PP), polyethylene terephthalate (PET), and polystyrene (PS) MP-DOM. After seven days of leaching, PVC reached a leaching concentration of 7.59 mg/L, and the other four microplastics reached approximately 4.5~4.7 mg/L. The leaching activity of PVC was considerably more active in an alkaline environment and under UV irradiation. All the fluorescence signals of MP-DOM components were located in the protein/phenol-like fluorescence region. The fact that C1 and C2 were found in every microplastic revealed that these substances took up quite a large proportion of MP-DOM. Protein/phenolic substances in MP-DOM showed different binding ability with different heavy metals, which can be realized from the log K values calculated for Cr3+ (3.99–5.51), Cu2+ (3.06–4.83), Cd2+ (3.76–4.41), and Fe3+ (3.11–5.03). This work introduced more MP-DOM samples, and offered spectroscopic insight into the characteristics and environmental fate of MP-DOM at a molecular level. Furthermore, this study displayed the potential applicability of using the integrated methods to track the MP-DOM formation process and environmental behavior in natural aquatic systems.